Insights from poverty maps for development and food relief program targeting: an application to Malawi - Benson, Todd (International Food Policy Research Institute, 2006)
This study aims to assess the value of poverty mapping to public-works projects undertaken by the World Food Programme (WFP) with the government of Malawi in its Food for Assets and Development (FFASD) program....Poverty mapping is a useful decisionmaking tool in targeting relief and development programs, and it provides objective and nonpolitical information that is also helpful in prioritizing areas for poverty alleviation projects and emergency food aid relief.